Application of Theory of Planned Behavior on Periodic Testing among People Living with HIV/AIDS in Jombang, East Java, Indonesia - Helmi Annuchasari; Argyo Demartoto; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: HIV/AIDS is one of the sexually transmitted diseases that is still high in the world. As many as 650,000 people died from this disease, around 38.4 million people were living with HIV/AIDS (PLWHA), by the end of 2021 with 1.5 million people newly infected with HIV. This study aimed to explore the behavior of people with HIV/AIDS based on the theory of planned behavior. Subjects and Method: A qualitative design with a case study approach was conducted at the Jombang District Health Service, Jombang Care Center, and the Kabuh Community Health Center Work Area. A total of 5 key informants, 10 people with HIV/AIDS as main informants, 1 supporting informant were selected purposively and snowballed. Data collection was carried out by interviews, observation, documentation (taking photos and reviewing control cards of people with HIV/AIDS). Data were analyzed using the Miles and Huberman method. Results: Behavioral intentions are related to the behavior of regular examinations in PLWHA. Attitudes are related to the behavior of regular examinations of PLWHA. Subjective norms are related to the behavior of regular examinations in PLWHA. Perceived behavioral control is related to the behavior of periodic examinations of PLWHA in Jombang Regency, East Java. Conclusion: Informants have high intentions or positive intentions to carry out periodic examinations aimed at maintaining their health so that it is much better. Informants accept and believe that with regular check-ups their body condition and health will be much better. The role of family and peer support groups is stronger than the influence of health workers. All key informants had positive control behavior to carry out examinations at community health centers that were not close to where they lived when the service from health workers was non-discriminatory and provided accurate information.